ANALISA GETARAN PADA BEARING BERBASIS KERUSAKAN BEARING - Rachman, Arief; Hartono, Budi; Yuliaji, Dwi (Universitas Ibn Khaldun Bogor, 2018)
Bearing is one part of the machine element that plays an important role. The function of the bearing is to support a shaft so that the shaft can rotate without excessive friction. Research was done to find out the value of vibration in a critical rotation test tool to determine the extent to which a rotating axle with a certain speed of the axis rotation. This test used a critical rotation testapparatus on a bar of carbon iron with diameter size D = 25.4 mm with L = 764 mm by using coupling. From experiments used rotation of 200 to 1000 rpm, the first experiment using 1000 rpm obtained a result of vertical axis obtained 9.5 mm/s with new bearing testing was performed using 5 variations ie new bearings, abrasion, corrosion, without lubrication, clutch that is not straight. The second experiment using a abrasion bearing of 1000 rpm resulted from a vertical axis 7 mm/s. The third experiment using corrosion bearing with 1000 rpm rotation resulted from a vertical axis of 3.4 mm / s. The fourth experiment using a lubrication bearing with rpm 1000 obtained the result of a vertical axis 9.6 mm / s. The fifth experiment using a non-straight coupling yielded 14.1 mm/s. The greater the bearing rotation value leads to a large twisting angle so that it impacts most semantic vibration values on the bearing.